Communication-based on local wisdom as a fortress of family resilience in the era of globalization: Experiences from Javanese speech culture - Muhammad Muhajir (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
This study discusses the urgency of communication in a family relationship. The author makes use of communication-based on Javanese local wisdom as an effort to build family resilience in the era of globalization. The method used is descriptive-analytic in explaining the communication based on Javanese local wisdom in the family is realized to build family resilience in the era of globalization. The results of this study show that the local wisdom of Java; 1)